Verfahren zur Herstellung von acylierten Proteinpuder - SCHRADER, WARREN E; BAKER, JEFFREY CLAYTON; MOSER, BRIAN A (2005)
A method for recovering an acylated protein as a powder, especially in cases where said acylated protein is one that resists isolation by isoelectric precipitation from aqueous solutions of the protein, said method comprising in combination adjusting said aqueous solution to near the isoelectric pH of the protein and providing a suitable alcohol concentration to cause precipitation of the protein in the form of filterable particles at said pH.